Analisis Akar Masalah Kekerasan dalam Rumah Tangga (KDRT) dalam Perspektif Feminis - Setiawan, Antonius Ian Bayu (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
Abstract: Domestic violence is one of the most common cases of violence against women. Domestic violence makes women helpless, physically injured, suffer psychologically, and can even cause death. The purpose of this research is to analyze the root causes of domestic violence and find solutions to prevent domestic violence. This research uses a literature study method. Researchers collect sources from books, journals, and other written literature. The analytical method uses descriptive analytical methods with the presentation of data qualitatively in the form of narrative text. There are several root causes of domestic violence problems, this can be seen from biological theory, frustration-aggression theory, and control theory. The form of prevention that can be done according to a feminist perspective is to promote gender equality and justice to create harmony and share a fair role in household dynamics. Feminists fight for women to get fair and empowered rights so that women don't get domestic violence. Family counselors have an important role in empowering victims and providing interventions to perpetrators. The interventions provided help to break the cycle of violence.